Differences in Water Consumption of Wheat Varieties Are Affected by Root Morphology Characteristics and Post-anthesis Root Senescence - Zheng, Xuejiao; Yu, Zhenwen; Shi, Yu; Liang, Peng (Frontiers in Plant Science, 2022)
Selecting high-yielding wheat varieties for cultivation can effectively increase water use efficiency (WUE) in the Huang¬–Huai¬–Hai Plain, where is threatened by increasing water shortages. To further identify the difference in water use and its relationship with root morphology and senescence characteristics, wheat varieties with different yield potentials—Yannong 1212 (YN), Jimai 22 (JM), and Liangxing 99 (LX)—were studied in a high-yielding wheat field. The water consumption percentage (CP) in YN decreased from planting to anthesis; however, crop evapotranspiration and CP increased from anthesis to maturity compared with JM and LX. In YN, a higher soil water consumption from anthesis to maturity in the 0–100 cm soil layer was partly attributed to the greater root weight density in the 20–60 cm soil layer. In topsoil (0–40 cm), root length density, root surface area density, and root diameter at 20 days after anthesis, root superoxide dismutase activity and root triphenyltetrazolium chloride reduction activity during mid grain filling stage were higher in YN than in JM and LX. YN had the highest grain yields of 9840 and 11462 kg ha-1 and increased grain yield and WUE by 12.0% and 8.4%, respectively, as compared to JM, and by 30.3% and 21.3%, respectively as compared to LX. Ensuring more soil water extraction post-anthesis by increasing roots in the 20-60 cm soil profile, improving root morphology traits, and alleviating root senescence in the topsoil during mid grain filling stage will assist selecting wheat varieties with high yield and WUE.